Use of diuretics and outcomes in patients with type 2 diabetes: findings from the EMPA‐REG OUTCOME trial. (28th June 2021) - Pellicori, Pierpaolo; Fitchett, David; Kosiborod, Mikhail N.; Ofstad, Anne P.; Seman, Leo; Zinman, Bernard; Zwiener, Isabella; Wanner, Christoph; George, Jyothis; Inzucchi, Silvio E.; Testani, Jeffrey M.; Cleland, John G.F.
Abstract: Aims: Loop diuretics (LD) relieve symptoms and signs of congestion due to heart failure (HF), but many patients prescribed LD do not have such a diagnosis. We studied the relationship between HF diagnosis, use of LD, and outcomes in patients with type 2 diabetes mellitus (T2DM) enrolled in the EMPA‐REG OUTCOME trial. Methods and results: The relationship between HF diagnosis, use of LD, and outcomes was evaluated in four patient subgroups with T2DM: (i) investigator‐reported HF on LD, (ii) investigator‐reported HF not on LD, (iii) no HF on LD, and (iv) no HF and not on LD, and we assessed their risk of cardiovascular events. Of 7020 participants, 706 (10%) had a diagnosis of HF at baseline, of whom 334 were prescribed LD. However, 755 (11%) patients who did not have a diagnosis of HF were prescribed LD. Compared to those with neither HF nor prescribed LD (reference group; placebo), those with both HF and receiving LD had the highest rates for all‐cause [hazard ratio (HR) (95% confidence interval) 3.19 (2.03–5.01)] and cardiovascular mortality [3.83 [(2.28–6.44)], and HF hospitalizations [9.51 (5.61–16.14)]. Patients without HF but prescribed LD had higher rates for all three outcomes [1.62 (1.10–2.39); 1.97 (1.26–3.08); 3.20 (1.90–5.39)], which were similar to patients with HF who were not receiving LD [1.42 (0.78–2.57); 1.56 (0.78–3.11); 3.00 (1.40–6.40)]. Empagliflozin had similar benefits regardless of subgroup ( P for interaction >0.1 for all outcomes). Conclusion: Patients with T2DM prescribed LD are at greater risk of cardiovascular events even if they are not reported to have HF; this might reflect under‐diagnosis. Empagliflozin was similarly effective in all subgroups investigated. Abstract : Cumulative incidence curves for the composite endpoint of heart failure (HF) hospitalization or cardiovascular (CV) mortality, and all‐cause mortality in patients with and without HF, who were prescribed or not a loop diuretic (LD). BL, baseline.